DETOUR CERTIFIED DOMINATION NUMBER OF GRAPHS - V.G. Bhagavathi Ammal,S. Darvin Shiny (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this paper, we introduce the concept of detour certified domination number of Graphs. Here we characterised graphs with and studied the relation of with other parameters. A subset S of V(G) is said to be a certified dominating set if it is a dominating set and every vertex of S has either zero or atleast two neighbours in V(G) – S. The certified domination number is the minimum cardinality of the certified dominating set and is denoted by . A set S of vertices of G is called a detour certified dominating set if S is a certified dominating set and every vertex of G lie in some detour of vertices of S. The minimum cardinality of a detour certified dominating set is the detour certified domination number of G and is denoted by